2012
DOI: 10.1186/1475-2891-11-79
|View full text |Cite
|
Sign up to set email alerts
|

Diverse effects of a low dose supplement of lipidated curcumin in healthy middle aged people

Abstract: BackgroundCurcumin extracts of turmeric are proposed to produce health benefits. To date, human intervention studies have focused mainly on people with existing health problems given high doses of poorly absorbed curcumin. The purpose of the current study was to check whether in healthy people, a low dose of a lipidated curcumin extract could alter wellness-related measures.MethodsThe present study was conducted in healthy middle aged people (40–60 years old) with a low dose of curcumin (80 mg/day) in a lipida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
152
5
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(164 citation statements)
references
References 35 publications
3
152
5
4
Order By: Relevance
“…Initially, several commercially available curcumin brands were analyzed for their absorption into the blood and brain, and the ratios of curcumin concentrations in the brain and red blood cells (RBCs) were determined in wild-type mice (Supplemental Figure 4). The highest brain concentrations were obtained with Longvida Optimized Curcumin formulation coated with lipophilic matrix (74,75) (Supplemental Figure 4). The optimal curcumin formulation, dose, and regimen were further calibrated through in vivo retinal amyloid imaging in double-transgenic APP SWE /PS1 ΔE9 mouse models (Supplemental Figure 5).…”
Section: Retinal Aβ and Neuritic-like Deposits Nft-like Structures mentioning
confidence: 98%
See 2 more Smart Citations
“…Initially, several commercially available curcumin brands were analyzed for their absorption into the blood and brain, and the ratios of curcumin concentrations in the brain and red blood cells (RBCs) were determined in wild-type mice (Supplemental Figure 4). The highest brain concentrations were obtained with Longvida Optimized Curcumin formulation coated with lipophilic matrix (74,75) (Supplemental Figure 4). The optimal curcumin formulation, dose, and regimen were further calibrated through in vivo retinal amyloid imaging in double-transgenic APP SWE /PS1 ΔE9 mouse models (Supplemental Figure 5).…”
Section: Retinal Aβ and Neuritic-like Deposits Nft-like Structures mentioning
confidence: 98%
“…Curcumin showed a distinct labeling pattern that was similar to the amyloid spots observed in living patients. Curcumin is considered as generally recognized as safe by the FDA based on previous clinical trials (74,75,104), and the Longvida curcumin used in this study caused minimal to no adverse effects. Longvida's safety has been demonstrated in pharmacokinetic studies in humans (105) and extensive toxicity testing in animals (106), and its efficacy has been demonstrated in two clinical trials (74,75).…”
Section: Klvffamentioning
confidence: 99%
See 1 more Smart Citation
“…This SLCP consists of high-purity, long-chain phospholipid bilayer and a long-chain fatty acid solid lipid core, which coats the Cur. The SLCP have been well characterized by Maiti et al [34] and by Cole and Frautschy laboratory, at the University of California, Los Angeles in collaboration with Verdure Science [26,[35][36][37]. Details sources of all the antibodies used in this study are summarized in Table 1.…”
Section: Chemicalsmentioning
confidence: 99%
“…26 In addition, DiSilvestro et al demonstrated that a low dose of Longvida (80 mg/day) imparted potentially healthpromoting effects in healthy middle-aged humans. 27 In addition, in a recent investigation, Longvida selectively suppressed soluble Tau dimers and corrected molecular chaperone, synaptic, and behavioral deficits in transgenic mice, suggesting that this curcumin formulation may have potential beneficial effects against Alzheimer's disease. 28 However, to date, the effects of this bioavailable curcumin preparation, namely, Longvida, on inflammation and inflammatory biomarkers remain unknown.…”
Section: Introduction Imentioning
confidence: 99%